2016
DOI: 10.1007/978-3-319-54687-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Blended Learning MOOC – A Study of One bMOOC in Norwegian Teacher Education

Abstract: Although MOOCs have been around for a decade, the use of MOOCs in teacher training is a new development. In 2015, a Norwegian teacher education received internal funding to develop a MOOC intended for blended learning, which we call bMOOC. The bMOOC consisted of four different modules, and the course content was created internally by highly competent teacher trainers. One goal with the bMOOC was to familiarize teacher students and teacher educators with the concept of blended learning. Another goal was to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Another argument for the broader perspective is found in the need for a deep technological understanding. This is foundational in the work of Lund et al (2014) but also an important part of several discussions in other articles (e.g., Brevik et al, 2019;Brox, 2017;Langseth & Haugsbakken, 2016). Despite not always containing an explicit link to common notions of digital competence, these articles still bring up important discussions about the implications of digitalisation for education and the challenges the field faces when attempting to relate to constantly evolving technologies.…”
Section: A Concept Outgrowing the Field?mentioning
confidence: 89%
See 2 more Smart Citations
“…Another argument for the broader perspective is found in the need for a deep technological understanding. This is foundational in the work of Lund et al (2014) but also an important part of several discussions in other articles (e.g., Brevik et al, 2019;Brox, 2017;Langseth & Haugsbakken, 2016). Despite not always containing an explicit link to common notions of digital competence, these articles still bring up important discussions about the implications of digitalisation for education and the challenges the field faces when attempting to relate to constantly evolving technologies.…”
Section: A Concept Outgrowing the Field?mentioning
confidence: 89%
“…These are 'resilience to digital distractions' and 'ICT self-efficacy'. Other authors use the quantitative approach to measure other aspects relevant to the study, e.g., the evaluation of courses or work form (Helgevold & Moen, 2015;Langseth & Haugsbakken, 2016;Lund & Vestøl, 2020), and the quantitative sections of these studies are thus less relevant to this discussion.…”
Section: Methods Used In Selected Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for designing an Educational Action Task Force "EATF", a flexible, collaborative and networked support unit that will support faculty to make online courses, is based on research and experiences acquired at a large Norwegian university. This research shows the increased need for putting focus on how online courses are made [1,2]. There is a demand for a technological infrastructure, and pedagogical support for faculties that wish to make high-quality online courses.…”
Section: Introductionmentioning
confidence: 93%
“…Developing micro-cultures, on the other hand, share an interest in innovation, creating and shaping new approaches and new ways of interacting in and outside the group. Research on higher education carried out in Norway found that the attitude to new technologies in these two types of micro-cultures may impede or encourage digitalization (Fossland 2015;Jacobsen 2017;Langseth & Haugsbakken 2016). Consequently, leaving digital professional development entirely to the meso-level is also not a sustainable strategy when it comes to developing well-informed digital practices in higher education.…”
Section: Digital Development In Institutional Settingsmentioning
confidence: 99%